Five-year outcomes of CD19 followed by CD22 chimeric antigen receptor T-cell therapy in B-cell acute lymphoblastic leukemia patients who relapsed after allo-transplantation - Shuangyou Liu; Lihong An; Zhichao Yin; Yuehui Lin; Zhuojun Ling; Biping Deng; Xinjian Yu; Qinlong Zheng; Defeng Zhao; Tong Wu; Alex H. Chang; Chunrong Tong (Haematologica)
Not available.